AKOMODASI ‘URF TERHADAP PEMAHAMAN FIQIH INDONESIA MASA LALU - AS, Susiadi (Universitas Islam Negeri Raden Intan Lampung, 2014)
‘Urf refers to custom that has been practiced by people and not against the Islamic-law or shari’a, it already becomes permanent law in society. The positive sides and goodness makes ‘Urf accommodated by many Indonesian scholars on Islamic missionary in this archipelago. This can be proved by the methods used by Walisongo in the development of Islamic law i.e. 'urf in tahlil and read Yasin whenever our family or relatives died. However, those implementation of ‘urf were initially habits of Hindus who did lamentations and cries on the death. Later, it was changed by scholars to became praises to God by read Shalawat and Yasin. Therefore Urf can be used as an establishing-method of law in accordance with fiqh-law